Moving up the global value chain in Latvia - Yashiro, Naomitsu (OECD Economics Department Working Papers, 2017)
Stronger integration in global value chains would speed up economic convergence to advanced OECD economies and raise living standards. Participation in global value chains (GVCs) offers opportunities for boosting productivity through knowledge transfer and intensive use of technologically advanced inputs. It also enables Latvia to diversify exports into high value added goods and services. Latvia's participation in GVC lags behind its Baltic and Central European peers. It also draws less value added from GVCs compared to many OECD economies. Nevertheless, GVC participation boosts the productivity of Latvian firms and enables them to increase employment and wages. Strong skills, high innovation capabilities and efficient resource allocation are essential for Latvian firms to engage in more knowledge intensive activities within GVCs. Improving access to higher education, promoting innovation cooperation between Latvian firms and foreign research institutes, reducing the large informal economy and establishing an effective judiciary and insolvency regime would unlock productivity growth through stronger integration in GVCs. This Working Paper relates to the 2017 OECD Economic Survey of Latvia. (www.oecd.org/eco/surveys/economic-survey-latvia.htm)